PENGARUH EXPERIENTIAL MARKETING TERHADAP LOYALITAS PENGUNJUNG DI BALI SAFARI & MARINE PARK, GIANYAR - Ni Wayan Anandhea Kurniadevi; Hanugerah Kristiono Liestiandre; Ida Bagus Putra Negarayana (Pusat Penelitian dan Pengabdian Kepada Masyarakat Politeknik Pariwisata Bali, 2022)
This study aims to determine the effect of experiential marketing on visitor loyalty at Bali Safari & Marine Park, Gianyar. This study used a quantitative approach through the distribution of online questionnaires by determining the sample, namely purposive sampling and the formula for large population samples. The sample in this study was 200 respondents consisting of domestic tourists and foreign tourists. The data in this study were analyzed using multiple linear regression analysis techniques. The results obtained by domestic tourists stated that experiential marketing variables including sense, act, and relate affect loyalty, but feel and think variables do not affect loyalty. Foreign tourists stated that experiential marketing variables including feel, think, and relate had an effect on loyalty, but the sense and act variables had no effect on loyalty. The findings also show that all respondents agree that experiential marketing variables including sense, feel, think, act, and relate silmutanly have an effect on visitor loyalty at Bali Safari & Marine Park Gianyar.